LEXICAL DENSITY AND READABILITY IN STUDENTS’ THESIS INTRODUCTIONS - Siregar, May Sarah; Hara, Nina Tiya; Sinar, Tengku Silvana (Ma Chung Press, 2024)
This study investigates lexical density and readability in students’ undergraduate thesis introductions. Documentation technique is used to collect the data while qualitative content analysis was employed as the method to present the data. The data of this study were content words and sentences taken from the data sources of 20 undergraduate’s thesis introductions. The scores of lexical density and readability were obtained by using Flesch Reading Ease Tool online. The findings show that all introductions exhibit high lexical density, with scores ranging from 51,28% to 68,08%. Whilst, the readability scores range from 10.92 to 17.58, and they are all categorized as being very difficult writings. In summary, the findings demonstrate that all thesis introductions exhibit a high level of complexity in their writing. These introductions showcase the deliberate use of rich and precise content words. Consequently, they pose a significant challenge for comprehension due to their density.